Lexicogrammatical Analysis of Narrative Texts Written by First Semester Students at Unika ST. Paulus Ruteng - Jelimun, Maria Olga; Suarnajaya, I Wayan; Sri Adnyani, Ni Luh Putu (Journal of Education Reseach and Evaluation, 2020)
This research conducted a qualitative investigation of the transitivity structure, language use and mood structure of narrative texts written by first semester students at UNIKA St. Paulus Ruteng. The data sources of this study were narrative texts written by students on the English study programme. The researchers investigated the dominant transitivity process and analysed the mood structure of the students’ narrative texts using Miles and Huberman’s interactive model. The researchers collected data from the curriculum documentation and by interviewing and giving exercises to the students. Furthermore, the instrument was the researchers and the students’ worksheets. The findings showed that six transitivity processes were applied in the students’ writing. The processes were the material process, mental process, verbal process, behavioural process, relational process and existential process. The dominant process used was the material process, since the texts written by the students mostly contained action verbs describing the characters’ physical actions. The second most common process was the relational process, which was followed by the mental process with 34.15%. The verbal process accounted for only 7.41%. The other processes contained in the texts were the behavioural process and the existential process, and affect, status and contact were as mood aspect.